2011
DOI: 10.1074/jbc.m110.214171
|View full text |Cite
|
Sign up to set email alerts
|

Anchor Peptide of Transferrin-binding Protein B Is Required for Interaction with Transferrin-binding Protein A

Abstract: Background: Transferrin receptors are critical for survival of important Gram-negative bacterial pathogens. Results: The anchoring peptide of TbpB mediates interaction with TbpA. Conclusion:The anchor peptide mediates the process by which TbpB captures transferrin and delivers it to TbpA. Significance: TbpB is critical for survival of important bacterial pathogens and this study provides insights to its role in acquiring iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Ferric iron can be imported into NTHI when the FhuABCD complex binds to ferrichrome and the Tbp1/Tbp2 proteins bind to transferrin (16,34,35,63,89). To our knowledge, though, there have been no published reports of ferrous iron uptake in NTHI.…”
mentioning
confidence: 80%
“…Ferric iron can be imported into NTHI when the FhuABCD complex binds to ferrichrome and the Tbp1/Tbp2 proteins bind to transferrin (16,34,35,63,89). To our knowledge, though, there have been no published reports of ferrous iron uptake in NTHI.…”
mentioning
confidence: 80%
“…Our data provide important new insights into the critical role of this region in the functionality of this lipoprotein. In fact, a recent study indicated that the "anchor peptide" of meningococcal TbpB, comprised of amino acids 2 to 40, contributes to the physical interaction between TbpA and TbpB, which is likely necessary for the cooperative activity of the two proteins (42). Further analysis showed that the interaction does not require the first seven amino acids, which contains the homologous polyglycine tract.…”
Section: Discussionmentioning
confidence: 96%
“…This feature is not present in the LbpB from M. bovis (Yu and Schryvers 2002). The selective release of LbpB from the meningococcal cell surface by NalP through proteolytic cleavage of the anchor peptide (Roussel-Jazede et al 2010) clearly would compromise anchor peptide facilitated transfer of Lf from LbpB to LbpA comparable to what is proposed for TbpB (Yang et al 2011). However, the expression of NalP is phase variable which provides the opportunity for efficient iron acquisition under appropriate conditions and release of LbpB when this would be advantageous (Oldfield et al 2013).…”
Section: R a F Tmentioning
confidence: 88%
“…However, the validity of extrapolating results to LbpBs from M. catarrhalis or Neisseria species would be questionable as the acquisition of the negatively charged regions may be shifting the primary function away from iron acquisition. Since LbpB primarly binds to iron-loaded hLf through the N-lobe it is reasonable to speculate that it would be capable of facilitating its capture and transfer to LbpA through the anchor peptide-mediated complex formation proposed for TbpB (Yang et al 2011). This could readily be accomplished in the absence of the phase variable expression of NalP (Oldfield et al 2013) under appropriate conditions on the mucosal surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation